Antibacterial and environmentally friendly chitosan/polyvinyl alcohol blend membranes for air filtration. (15th October 2018) - Wang, Zhen; Yan, Feng; Pei, Hongchang; Li, Jianxin; Cui, Zhenyu; He, Benqiao
Graphical abstract: Highlights: CS and PVA are miscible due to an intermolecular hydrogen bond between them. CS/PVA membrane with a gradient interconnected structure was prepared via NIPS. 95.59% of air filtration efficiency and pressure drop of 633.5 Pa were achieved. Antibacterial rate of blend membrane was 94.8% for E. coli & 91.3% for S. aureus . Mechanism of air filtration is mainly attributed to surface direct interception. Abstract: An antibacterial and environmentally friendly chitosan (CS) /polyvinyl alcohol (PVA) blend membrane for air filtration was prepared via nonsolvent induced phase separation (NIPS) method. The chemical structure, thermal behavior, morphology, mechanical property and surface charge of the resultant CS/PVA membranes were characterized. Results showed that CS and PVA were miscible due to the intermolecular hydrogen bond between them. The blend membrane obtained from over 20 wt.% CS concentration exhibited a gradient interconnected porous structure without skin layer. The air filtration efficiency and pressure drop obtained from CS/PVA membrane with 30 wt.% CS concentration and the thickness of 37 μm under a face velocity of 5.3 cm s −1 were 95.59% and 633.5 Pa, respectively. The performance of air filtration obtained is mainly attributed to the direct interception of membrane surface. Further, the antibacterial rate of the blend membrane was up to 94.8% for E. coli and 91.3% for S. aureus .